2022
DOI: 10.1002/ecs2.4272
|View full text |Cite
|
Sign up to set email alerts
|

Winter and summer storms modify chlorophyll relationships with nutrients in seasonally ice‐covered lakes

Abstract: At broad spatial scales, primary productivity in lakes is known to increase in concert with nutrients, and variables that may disrupt or modify the tight coupling of nutrients and algae are of increasing interest, particularly for those shifting with climate change. Storms may disrupt algae–nutrient relationships, but the expected effects differ between winter and summer seasons, particularly for seasonally ice‐covered lakes. In winter, storms can dramatically change the under‐ice light environment, creating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Our findings also point to the importance of considering the recent history of local weather (e.g., high wind events) as an additional control, superimposed on seasonal variability, on contemporaneous distributions of plankton in temperate lakes. A number of studies have found weather events can be key drivers to lake plankton communities, particularly phytoplankton, through vertical mixing or supply of nutrients (Langenberg et al 2003; Stockwell et al 2020; Hampton et al 2022). Our results highlight the potential value that biologically focused sampling could provide for insights into the recent history of the physical structure (i.e., stratification‐mixing) of the lake, emphasizing the value of time‐resolved sampling for mechanistic insight into processes shaping the distributions of microorganisms in aquatic systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also point to the importance of considering the recent history of local weather (e.g., high wind events) as an additional control, superimposed on seasonal variability, on contemporaneous distributions of plankton in temperate lakes. A number of studies have found weather events can be key drivers to lake plankton communities, particularly phytoplankton, through vertical mixing or supply of nutrients (Langenberg et al 2003; Stockwell et al 2020; Hampton et al 2022). Our results highlight the potential value that biologically focused sampling could provide for insights into the recent history of the physical structure (i.e., stratification‐mixing) of the lake, emphasizing the value of time‐resolved sampling for mechanistic insight into processes shaping the distributions of microorganisms in aquatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…With cooling through the fall and winter, vertical mixing homogenizes lake waters, impacting the distribution of organisms (Okazaki and Nakano 2016). Superimposed on such seasonal changes, episodic events (e.g., storms) can alter water column structure with associated impacts on plankton productivity and biomass distributions (Stockwell et al 2020; Hampton et al 2022). To date, it remains mostly unknown how such dynamics might alter the distribution of microorganisms, thereby impacting specific ecosystem functions.…”
mentioning
confidence: 99%
“…Initial analyses with these data revealed winter as a time with often surprisingly high standing biomass of primary producers (algae), with active grazers and microbial processes (Hampton et al, 2017). Next, we sought to determine whether climate and local weather could help explain variation in algal biomass, as storms can alter the light environment during winter and may alter both nutrients and light during the summer months (Hampton et al, 2022). Complex data assembly was necessary for the project's larger goal of inferring weather conditions during two times of the year when we did not have in situ data-the time at which ice formed each year and the time before summer sampling began.…”
Section: A C a S E S Tudy With Ta Rgetsmentioning
confidence: 99%
“…For example, Kepler (Altintas et al, 2004) and the targets and drake r packages (Landau, 2018(Landau, , 2021b are three prominent examples of WMS that have seen use in the fields of ecology and evolution (e.g. Hampton et al, 2022). A major benefit of WMS is the capacity to track the status of all required files and functions to prevent steps in a larger pipeline from being skipped and by ensuring that data are kept up to date as models or harmonization routines change.…”
Section: Introductionmentioning
confidence: 99%
“…In many lakes, nutrients are often higher in the winter than in the summer (Hampton et al 2017), and convection with clear-ice conditions can keep nutrients in the photic zone (Kelley 1997), suggesting that nutrients may not limit phytoplankton growth during the winter (Vasseur et al 2005). However, an increasing number of studies suggest that nutrient limitation or nutrient availability may also play a role in shaping phytoplankton dynamics in the winter (Özkundakci et al 2016;Hampton et al 2022;Hrycik et al 2022). For example, Aulacoseira skvortzowii, a diatom that can be suspended in the water column or attached to ice, can reach bloom levels in Lake Baikal in the winter (Katz et al 2015).…”
mentioning
confidence: 99%